PHANEROZOIC RECORD OF PLATE TECTONIC CONTROL OF SEAWATER CHEMISTRY AND CARBONATE SEDIMENTATION - Steuber T.; Veizer J. (My University, 2002)
Sr concentrations in Phanerozoic biological calcite suggest a close link between fluctuations in the Sr/Ca ratio of seawater, aragonite versus calcite sedimentation, and the Mg/Ca ratio of seawater, the entire chain being driven by the rate of production and hydrothermal alteration of the oceanic crust. Model simulations suggest that variations in hydrothermal and continental weathering fluxes cannot be the sole reason for the observed Phanerozoic seawater Sr/Ca trend. Changing Sr burial in marine carbonates is likely the most important mechanism that can explain the experimental data. During episodes of high seawater Mg/Ca ratios, aragonite was preferentially deposited, resulting in low seawater Sr/Ca ratios. At low Mg/Ca ratios, calcite was the dominant carbonate sediment, and the Sr/Ca ratio of seawater was high. The evidence for changing chemistry of seawater also has implications for the application of the Sr/Ca and Mg/Ca paleothermometers, in particular for pre-Quaternary samples, and for the assessment of diagenetic alteration of fossil skeletal carbonates by using Sr/Ca ratios.
Keywords: seawater; strontium; calcite; geochemical models; Phanerozoic